Use of survival analysis methods with cattle reproductive performance data - Sherington, J.; Tegegne, Azage (Biometric Society of Zimbabwe, 1992)
The paper gives an example of the use of survival analysis to examine time to conception for a breed by nutrition factorial experiment and the relationship between time to conception and body weight. The example is made complicated by confounding between the treatments and the weight of animals at the beginning of mating. The paper first describes the experiment briefly. It then describes an analysis of simple conception rate using logistic models. Survival analysis is then outlined and the proportional hazards model is used to analyse time to conception.